Design and control of variable field permanent magnet motors. Issue 7 (25th March 2019) - Matsui, Nobuyuki
Abstract : This is a survey paper focusing on permanent magnet motors with variable field capability. The synchronous motors, which have been applied to somewhat limited fields, have garnered attention as attractive electric drives. Due to a connection with rare‐earth magnet and power electronics‐based flexible control, current permanent magnet synchronous motors have achieved the best position in terms of high power and torque densities, high efficiency and flexible control capability. In order to satisfy the diverse demands of users, a motor is requested to ensure high‐efficiency operation at multiple operating points on the speed–torque plane. It is well recognized that maximum efficiency is attained under the condition that the copper loss is equal to the fixed loss, mainly composed of iron loss, at a given operating point. This is why permanent magnet synchronous motors should have the capability of adjusting the field excitation, similar to the direct current shunt motors. In this paper, recent trends of research and development of variable field permanent magnet motors are overviewed from the standpoint of design and control. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.